The study of students satisfaction of blended learning: a survey in UiTM / Nor Maziati Bakar - Bakar, Nor Maziati (2013)
In this paper, a study about students' satisfaction of blended learning system in University Technology Mara (UiTM) are discussed. Blended learning was introduced to UiTM students and lecturers since 2009. This facility was provided by i-Learn Centre, together with Academic Affairs Division. In higher education, methods either traditional or using technology are used in their learning process. Organizations must use a blend of learning approaches in their strategies to get the right content in the right format to the right people at the right time. Blended learning combines multiple delivery media that are designed to complement each other and promote learning and application-learned behavior (if. Singh, 2003). This research also study on the reliability between 5 variables measured. Questionnaire was distributed via online and covered on 5 variables scale items that adopted from J. B. Arbaugh (2000); 1) perceived usefulness and ease of use, 2) perceived flexibility, 3) perceived course quality, 4) perceived course interaction, and 5) perceived student satisfaction. Participants are randomly selected from any faculty at UiTM. Furthermore, nowadays student used e-learning (digitally delivered learning) programs tended to be a repetition or compilation of online versions of classroom based courses. Keyword: blended learning, online learning, student satisfaction.